APOE missense variant R145C is associated with increased Alzheimer's disease risk in African ancestry individuals with the APOE 3/4 genotype. (20th December 2022) - Guen, Yann Le; Belloy, Michael E; Eger, Sarah J; Chen, Annabel; Kennedy, Gabriel; Thornton, Timothy A; Farrer, Lindsay A.; Napolioni, Valerio; He, Zihuai; Greicius, Michael D
Abstract: Background: The APOE gene has two common missense variants that greatly impact the risk of late‐onset Alzheimer's disease (AD). Here we examined the risk of a third APOE missense variant, R145C, that is rare in European‐Americans but common in African‐Americans and always in phase with APOEε3 (Table 1 ). Method: We included 11, 790 individuals of African ancestry (Table 2 ). The discovery sample was composed of next generation sequencing data (2, 888 cases and 4, 957 controls), and the replication was composed of imputed data (1, 201 cases and 2, 744 controls). In primary analyses, the AD risk associated with R145C was estimated using a linear‐mixed‐model regression on case‐control diagnosis. In secondary analyses, we estimated the influence of R145C on age‐at‐onset using linear‐mixed‐model regression, and risk of conversion to AD using competing risk regression. Result: In ε3/ε4 ‐stratified meta‐analyses (Table 3 ), R145C carriers had a nearly three‐fold increased risk compared to non‐carriers (OR=2.75[1.84;4.11]; P=8.3x10 ‐7 ) and had a reported AD age‐at‐onset nearly 6 years younger (β=‐5.72[7.87;3.56]; P=2.0x10 ‐7 ). Competing risk regression showed that the cumulative incidence of AD grows faster with age in R145C carriers compared to non‐carriers (HR=2.42[1.81;3.25]; P=3.7x10 ‐9 ; Figure 1 ). Conclusion: The R145C variant is a potent risk factor for AD among African ancestry individuals with the ε3/ε4 genotype. Our findings should enhance AD risk prediction in African ancestry individuals and help elucidate the mechanisms linking the apoE protein to AD pathogenesis. The findings add to the growing body of evidence demonstrating the importance of including ancestrally‐diverse populations in genetic studies.